Język polski: English - Język polski, Język polski (Management and Administration Journal, 2021)
Quantitative and structural changes in the employment of workers with disabilities aredependent on technology, technology and competence of the organization. Organizations shape so highly developed. approach open to all able-bodied and disabled workers and the diversification of skills. Claiming (it seems rightly) that there is no disabled workers are employees ofdifferent needs. This approach to employment and job adjustment is appropriate, does not exclude the needs of professional people. The article presents the importance of ergonomicsin the process of creating jobs in the example project conditions ERGO WORK.